Determinants of islamic banking profitability in Malaysia / Fauziah Abdullah - Abdullah, Fauziah (2007)
This paper is analyzing the factors which contribute to the profitability of Islamic banking. The proxy for profitability are four measures of performance are used in this study which is net non-interest margin (NIM), profit margin (BTP/TA), returns on assets (ROA), and returns on equity (ROE). The set of ratios used comprises fund source management (CSTFTA), funds use management (OVRHD/TA and NIEATA), and leverage and liquidity ratios (LOANTA) represent the bank characteristic. By examines this internal indicator this could help to determine which factors have a strong relation with profitability. The samples collected for this research are taken from 2 Islamic banks in Malaysia which is Bank Islam Malaysia Berhad (BIMB) and Bank Muamalat from year 1996-2006. Using a regression analysis for this research will help to estimate the factors could bring profitability of Islamic banking. Regression results indicate a strong positive correlation between profitability and the indicators after confirms previous finding.